2020
DOI: 10.1001/jamanetworkopen.2020.13793
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Longitudinal Trajectories of Cognitive and Social Activities and Brain Health in Old Age

Abstract: This cohort study examines trajectories of cognitive and social activities from midlife to late life and evaluates whether these trajectories are associated with brain structure, functional connectivity, and cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Another study on community-dwelling individuals found that those with higher tongue pressures were more socially active than those with lower tongue pressures [ 19 ]. On the other hand, social activities for the elderly reduced their risk of cognitive decline [ 32 ]. Thus, the deterioration of oral function might be associated with cognitive decline resulting from decreased rates of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on community-dwelling individuals found that those with higher tongue pressures were more socially active than those with lower tongue pressures [ 19 ]. On the other hand, social activities for the elderly reduced their risk of cognitive decline [ 32 ]. Thus, the deterioration of oral function might be associated with cognitive decline resulting from decreased rates of activity.…”
Section: Discussionmentioning
confidence: 99%
“…WM features including global and tract‐specific estimates of fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD), and mode of anisotropy (MO) were derived using 48 standard‐space masks available from the ICBM‐DTI‐81 White‐Matter Labels Atlas (Mori, Wakana, van Zijl, & Nagae‐Poetscher, 2005; Wakana et al, 2007). Prior to this step, the diffusion‐weighted images were preprocessed using a combination of FSL's tools, including Top Up to correct for eddy currents and head motion, DTIFIT to fit the diffusion tensor and extract images for each metric of interest (e.g., FA and RD images), which was followed by tract‐based spatial statistics for registration and extracting FA/MD/AD/RD/MO skeletons for each individual (for further details, see supplementary methods in Anatürk et al (2020). Global WM hyperintensity (WMH) volumes were automatically extracted from FLAIR images with Brain Intensity AbNormality Classification Algorithm, as described in Griffanti et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…However, summarizing measures across brain regions and cognitive domains cannot provide information about specialized cognitive networks potentially linked to regional brain characteristics. Combined with models that estimate regional brain aging patterns (de Lange, Anatürk, et al, 2020;Eavani et al, 2018;Kaufmann et al, 2019;Smith et al, 2020), a development of processspecific cognitive models may provide a more detailed and accurate estimate of the relationship between brain and cognitive maintenance. Furthermore, dynamic brain processes that are not captured by structural measures may play an important role in reserve mechanisms (Franzmeier et al, 2017;Sala-Llonch et al, 2012).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…White-Matter Labels Atlas (Mori, Wakana, van Zijl, & Nagae-Poetscher, 2005;Wakana et al, 2007). Prior to this step, the diffusion-weighted images were preprocessed using a combination of FSL's tools, including Top Up to correct for eddy currents and head motion, DTIFIT to fit the diffusion tensor and extract images for each metric of interest (e.g., FA and RD images), which was followed by tract-based spatial statistics for registration and extracting FA/MD/ AD/RD/MO skeletons for each individual (for further details, see supplementary methods in Anatürk et al (2020). Global WM hyperintensity (WMH) volumes were automatically extracted from FLAIR images with Brain Intensity AbNormality Classification Algorithm, as described in Griffanti et al (2016).…”
Section: Mri Featuresmentioning
confidence: 99%